Influence of pH and Xanthan Gum on long-term stability of crayfish-based emulsions. (November 2017) - Felix, M.; Romero, A.; Guerrero, A.
Abstract: The present work focus on the evaluation of crayfish protein concentrates, surplus from crayfish processing industry, in the formation and stabilization of high-oleic O/W emulsions as a function of pH values (3.0, 5.0 and 8.0) and Xanthan Gum (XG) concentrations (0.06, 0.12, 0.25 and 0.50 wt.%). The emulsion microstructure and stability were determined through droplet size distributions (DSD) and rheological measurements, which were determined by means of Small Amplitude Oscillatory Shear (SAOS) measurements, over the ageing time. In addition, backscattering measurements were carried out to describe the destabilization mechanism. DSD profiles confirm that emulsions at pH 3.0 are not flocculated and they are stable over the ageing time studied. However, at pH 5.0 and 8.0 flocculation and further coalescence phenomena takes place. Rheological characterisation reveals a strong dependence of linear viscoelastic properties on XG concentration. In addition, viscoelastic properties also suggest that electrostatic interactions leads to the formation of an enhanced protein/polysaccharide network at pH 3.0. Graphical abstract: Highlights: The stability of CF-based emulsions depends on the pH value and XG concentration. High concentration of XG induces coalescence of droplets by depletion flocculation. Protein-XG interactions seem to control the destabilization of the emulsions studied. Viscoelastic properties seem to be governed by protein-polysaccharide interactions.